1. PERAN POLISI DAERAH JAWA TENGAH DALAM MENANGGULANGI TERORISME DI JAWA TENGAH PADA PERIODE 2009-2014 - Tri Puji A; Reni Windiani; Mohammad Rosyidin (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
This research aims to observe what role conducted by Polda Jateng against terrorism issue.Terrorism is one of the trasnational crime which has frightening effects.Central Java is oneof the province which has a many cases of terrorism from 2009 until 2014. Polda Jateng isan institution that has a role inlaw enforcement andcombating terrorism.This research usesqualitative method with necessary type of descriptive. The data were collected from bothprimary and secondary sources to describe every single roles conducted by Polda Jateng.The result shows that Polda Jateng has a role to preserve the crime scene in everyprosecution case of terrorism.